Implementasi Sistem Pengendalian Inventory Berbasis Website pada UMKM Otw29.Nasi Padang Vegetarian - Yulfiswandi, Yulfiswandi; Licca, Vellia (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to implement a web-based inventory control system at OTW29 Nasi Padang Vegetarian to improve stock management efficiency. Previously, inventory records were managed manually, leading to frequent inaccuracies and disruptions in operational processes. The developed system integrates the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods to determine optimal order quantities and reorder levels. The implementation results show that the system is capable of providing real-time stock information, increasing recording accuracy, and supporting faster and more precise raw material ordering decisions. The system has proven effective in reducing the risk of stockouts or overstocking and enhancing the overall operational efficiency of the MSME.